Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Chapter 2: Te Tiriti o Waitangi: A Blueprint for the Future - Campbell, Bronwyn (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 1: Colonial Theories of the State: Māori/State Relations - Tomlins-Jahnke, Huia (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: constitution; imperialism; tiriti o waitangi/treaty of waitangi

Comparative Constitutional Law and Indigenous Peoples: Canada, New Zealand and the USA - Claire Charters (Comparative Constitutional Law, 2011)
Keywords: constitution; crown law; crown policy; kāwanatanga; voting